Potensi Rhizobakteri Tanaman Jahe Merah (Zingiber officinale Linn. Var Rubrum) di Kabupaten Halmahera Utara sebagai Agen Pemacu Pertumbuhan Tanaman - Cornelia Dolfina Maatoke; Oktovianus Oktovianus (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Rhizobacteria are a type of bacteria that live in the area of plant roots, these bacteria are able to have a positive influence on plant growth. Various bacteria that have the potential to promote plant growth are thought to be in the red ginger root area. The purpose of this study was to determine the ability of red ginger rhizobacteria in dissolving phosphate, nitrogen fixing, IAA production and the effect of the rhizobacterial treatment on seed viability. The research was conducted at the Laboratory of MIPA Terpadu, Halmahera University, and further analysis at the Microbiology Laboratory, Bogor Agricultural University. Soil sampling at six locations, namely: Gosoma, Kusuri, Pitu, Ruko, Wari, and WKO villages. The research method used included the stages of sampling by purposive sampling, selection and characterization stages as well as potential test stages for rhizobacterial treatment on seed growth. The results showed that rhizobacteria with isolate code Rk. 3.1., Rk. 3.2., Rk. 3.3., and Rk. 3.4., was able to dissolve phosphate by 5.46 mm, 5.49 mm, 4.60 mm, and 3.18 mm, fixing nitrogen by 1289.50 µmol. m-1g1., 1329.47 µmol. m-1g1., 418.25 µmol. m-1g1., and 388.15 µmol. m-1g1., produced IAA growth hormone of 33.80 ppm, 35.72 ppm, 20.52 ppm, and 25.74 ppm, and had a significant effect on the growth of germination, growth simultaneity, maximum growth potential, and seed vigor index. Based on this study, it can be concluded that the isolates Rk. 3.1., Rk. 3.2., Rk. 3.3., and Rk. 3.4., can be used as plant growth promoting biological agents.